2020
DOI: 10.1042/bsr20201175
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer cells promote osteoclastogenesis and bone destruction through regulating EGF/ERK/CCL3 pathway

Abstract: Bone metastasis of colorectal cancer (CRC) cells leads to osteolysis. Aberrant activation of osteoclasts is responsible for bone resorption in tumor. In general, bone marrow-derived monocytes (BMMs) differentiate into osteoclasts, however, how CRC cells interact with BMMs and how to regulate the differentiation is elusive. We here report that CRC cells promote bone resorption in bone metastasis. Transcriptomic profiling revealed CCL3 up-regulated in MC-38 conditional medium treated BMMs. Further investigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Previously, in cases with GAgP, rs2237051 AA genotype is suggested to elevate the level of serum EGF [ 13 ]. EGF plays a crucial role in inflammation and tissue repair, serving as an important regulator in the process of periodontitis and bone destruction [ 24 , 25 ]. It is also involved in the regulation of tissue immune response, inhibits collagen synthesis by fibroblasts and affects osteoclast bone resorption, which plays an important role in periodontitis [ 24 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, in cases with GAgP, rs2237051 AA genotype is suggested to elevate the level of serum EGF [ 13 ]. EGF plays a crucial role in inflammation and tissue repair, serving as an important regulator in the process of periodontitis and bone destruction [ 24 , 25 ]. It is also involved in the regulation of tissue immune response, inhibits collagen synthesis by fibroblasts and affects osteoclast bone resorption, which plays an important role in periodontitis [ 24 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…EGF plays a crucial role in inflammation and tissue repair, serving as an important regulator in the process of periodontitis and bone destruction [ 24 , 25 ]. It is also involved in the regulation of tissue immune response, inhibits collagen synthesis by fibroblasts and affects osteoclast bone resorption, which plays an important role in periodontitis [ 24 , 26 , 27 ]. High levels of EGF can be detected in patients with oral diseases and are believed to be closely related to the occurrence and development of periodontitis [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported that CRC cell-derived Epidermal Growth Factor (EGF) activates BM-derived monocytes and stimulates their high CCL3 expression. CCL3 promotes osteoclast maturation and, consequently, osteoclastogenesis [38]. Another interaction implicated in cancer cell recruitment has been demonstrated between CXCR4, expressed in CRC cells, and CXCL12, located in BM-derived cells.…”
Section: Crc and Bone Marrowmentioning
confidence: 96%
“…The metastatic tropism is due to the interactions between ligands present on cancer cells and their specific receptors present on the cells of certain organs, or vice versa. Gong ZC et al [38] very recently showed the relevance of CCL3, expressed by BM-derived monocytes, in osteoclastogenesis in CRC bone metastases. The authors reported that CRC cell-derived Epidermal Growth Factor (EGF) activates BM-derived monocytes and stimulates their high CCL3 expression.…”
Section: Crc and Bone Marrowmentioning
confidence: 99%
“…Moreover, we further performed a cytokine array analysis, and HM-macrophages coculture caused a significant increase in many inflammatory cytokines (G-CSF, GM-CSF, sICAM1, IL-𝛼, IL-1𝛽, IL-1RA, IL-6, CCL3, and TNF𝛼), which are known to be abundantly present in ovarian cancer ascites (Figure 4l). [30] Chemokine (C-C motif) ligand 3 (CCL3) (also known as macrophage inflammatory protein 1 𝛼 (MIP-1𝛼)), is associated with metastasis of various tumor types such as renal cell and colorectal cancer, [31][32][33] and was shown to mediate macrophage retention in the metastatic sites of breast cancer. [35] Since the cytokine array analysis revealed a specific increase of CCL3 in the HM-macrophage coculture, we next investigated the role of CCL3 in the crosstalk.…”
Section: Hm Induces Tam-like Phenotypes In Macrophages and Enhances C...mentioning
confidence: 99%